MENDETEKSI PERUBAHAN PENGGUNAAN LAHAN SECARA SPASIAL DAN TEMPORAL DI BANDARA INTERNASIONAL YOGYAKARTA PADA CITRA GOOGLE EARTH - ning, Yuningsih (Universitas Negeri Padang, 2024)
Construction of the New Yogyakarta Kulon Progo International Airport (YIA) is one of the national development goals, especially in the aviation industry. A large Yogyakarta International Airport (YIA) construction project uses community-owned land. This research aims to determine and analyze the spatiotemporal characteristics of changes in land use in the new airport area of ​​Yogyakarta International Airport based on Google Earth Imagery of Kulon Progo Regency in 2017, 2020, and 2023. Changes in land use at the new airport of Yogyakarta International Airport show that from 2017 to 2023, land use has changed rapidly. Changes in land use in residential areas were -189 houses, population was -756 people, vegetation was -19.73 ha, and open land was -282.59 Ha, reduced due to the construction of the New Yogyakarta International Airport with significant transformation. Keywords: spatial-temporal, land use change, airport YIA, Google Earth Data